HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN PADA IBU PRIMIGRAVIDA TRIMESTER III DI PUSKESMAS SONDER - Menajang, Novita Klaudya; Pondaag, Linnie; Kundre, Rina (JURNAL KEPERAWATAN, 2017)
Abstract : Primigravida Pregnancy is a condition that causes physical and psychological changes. World Health Organization (WHO, 2014) maternal mortality rate (MMR) reached 289,000 (Health News, 2015). The purpose of this study was to determine the relationship of husband support the anxiety levels in Primigravida third trimester at Puskesmas Sonder. The study design used is cross sectional. The sample included 30 mothers, sampling technique samples using purposive sampling. Results showed support husband at Puskesmas Sonder most with the support of a good number of 23 people (76.7%) and the least with no support either a number of 7 people (23.3%). Lower anxiety levels in Primigravida Trimester III of 4 people (13.3%), medium anxiety as many as 23 people (76.7%), and high anxiety as much as 3 (10.0%). Bivariate analysis using Chi-square test p-value 0.007. The conclusion that there is a significant relationship between husband support with Anxiety Levels in primigravida Trimester III in Puskesmas Sonder. Suggestions research is expected to provide a reference for the development and study of science education in the field of Maternity Nursing Keywords: Support Husband, Anxiety Levels Abstrak : Kehamilan primigravida merupakan suatu kondisi yang menimbulkan perubahan fisik dan psikologis. World Health Organization (WHO, 2014) angka kematian ibu (AKI) mencapai 289.000 (Warta Kesehatan, 2015). Tujuan penelitian ini adalah untuk mengetahui Hubungan dukungan suami dengan tingkat kecemasan pada ibu primigravida trimester III di Puskesmas Sonder. Desain penelitian yang digunakan adalah cross sectional. Sampel berjumlah 30 ibu, teknik pengambilan Sampel menggunakan purposive sampling. Hasil Penelitian menunjukkan Dukungan Suami di Puskesmas Sonder yang paling banyak dengan dukungan baik sejumlah 23 orang (76.7%) dan yang paling sedikit dengan dukungan tidak baik sejumlah 7 orang (23.3). Tingkat kecemasan rendah pada ibu Primigravida Trimester III sebanyak 4 orang (13.3), kecemasan menengah sebanyak 23 orang (76.7), dan kecemasan tinggi sebanyak 3 orang (10.0). Analisi bivariate menggunakan uji Chi-square p value 0.007. Kesimpulan yaitu terdapat Hubungan yang signifikan antara Dukungan Suami dengan Tingkat Kecemasan pada Ibu Primigravida Trimester III di Puskesmas Sonder. Saran penelitian ini diharapkan dapat memberikan referensi bagi perkembangan dan kajian ilmu pendidikan dibidang Keperawatan Maternitas Kata Kunci : Dukungan Suami, Tingkat Kecemasan